2010
DOI: 10.1074/jbc.m109.038604
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Suppresses Activator Protein-1 Transcriptional Activity and Cyclooxygenase-2 Expression in Macrophages

Abstract: SIRT1 (Sirtuin type 1), a mammalian orthologue of yeast SIR2 (silent information regulator 2), has been shown to mediate a variety of calorie restriction (CR)-induced physiological events, such as cell fate regulation via deacetylation of the substrate proteins. However, whether SIRT1 deacetylates activator protein-1 (AP-1) to influence its transcriptional activity and target gene expression is still unknown. Here we demonstrate that SIRT1 directly interacts with the basic leucine zipper domains of c-Fos and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 44 publications
8
135
1
3
Order By: Relevance
“…Our previous work demonstrated SIRT1 suppresses the transcriptional activity of AP-1 [15]. Moreover, SIRT1 inhibits NF-B transcriptional activity [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work demonstrated SIRT1 suppresses the transcriptional activity of AP-1 [15]. Moreover, SIRT1 inhibits NF-B transcriptional activity [12].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 acts to protect the heart from hypertrophy, metabolic dysregulation and inflammation [11]. Moreover, SIRT1 inhibits NF-B and AP-1 transcriptional activity and the expression of downstream inflammatory genes [12][13][14][15]. We have previously shown that transgenic mice that overexpress SIRT1 in the vascular endothelium have better endothelium-dependent vasodilation and fewer atherosclerotic lesions when fed a high-fat diet [16].…”
mentioning
confidence: 99%
“…However, TLR4 stimulation has also been demonstrated to induce nicotinamide phosphoryltransferase-1 (Nampt1), an enzyme involved in NAD + synthesis, at later time-points, and this would enhance Sirt1 activity and thus dampen NF-kB-dependent responses, resulting in a negative-feedback effect. Sirt1 impaired the activity of another proinflammatory transcription factor, activating protein 1 (AP-1), in macrophages by targeting its subunits c-Jun and c-Fos [14], and thereby decreased transcription of the AP-1-dependent gene encoding cyclooxygenase 2 (COX2), an enzyme required for the synthesis of PGs. In a similar manner, Sirt1 deacetylates HIF-1a and prevents its interaction with p300, a transcriptional coactivator required for its activity [15].…”
Section: Nad + and Sirtuins As Regulators Of Inflammationmentioning
confidence: 99%
“…In a recent study, Gao and coworkers showed that c-Jun transcriptional activity can be downregulated by SIRT1 in vitro [37]. A second study rapidly followed, showing that c-Jun is actively deacetylated by SIRT1 in vivo [38], while a third team reported that both the subunits c-Jun and c-Fos are targeted by SIRT1 [39]. These events play a major role in regulating the function of several immune cells.…”
Section: Sirt1 Inhibits Ap-1 By Deacetylating C-jun and C-fosmentioning
confidence: 99%
“…These events play a major role in regulating the function of several immune cells. Indeed, in macrophages, SIRT1 activation was reported to decrease the transcription of COX-2, a typical AP-1 dependent pro-inflammatory gene [39].…”
Section: Sirt1 Inhibits Ap-1 By Deacetylating C-jun and C-fosmentioning
confidence: 99%